Historical Syntax of the Indo-European Languages : Part 1 - Petit, Daniel, (Language and Linguistics E-Books Online, Collection 2025., 2025)
This book provides an introduction to the historical syntax of the Indo-European languages. It aims to provide an overview of the main issues concerning the comparison of syntactic structrures within the language family and the reconstruction of their common ancestor.